Does single parenthood increase the probability of teenage promiscuity, drug use and crime? - Heather Antecol; Kelly Bedard (Claremont McKenna College, Department of Economics, 2002)
There is longstanding evidence that children raised by single parents are more likely to perform poorly in school and partake in 'deviant' behaviors such as smoking, sex, substance use and crime at young ages. However, as of yet there is not widespread evidence or agreement as to whether or not the timing of the marital disruption differentially impacts youth outcomes. Using the National Longitudinal Survey of Youth (NLSY) and the NLSY Young Adult Supplement, we find that the longer the biological father remains in the household the lower the probability that youth engage in sexual activity. In contrast, it is youth whose fathers are never present who are more likely to be convicted of a crime, youth whose fathers leave during adolescence who are more likely to drink alcohol and use illegal drugs and youth whose fathers leave during childhood who are more likely to smoke cigarettes.
Keywords: J12; D1; E21; 330; Family Structure; Marital Dissolution; Youth Outcomes; Alleinerziehende; Jugendliche; Sexualität; Drogenkonsum; Jugendkriminalität; USA